heureka

avatar
Имя пользователяheureka
Гол18542
Stats
Вопросов 11
ответы 3206

 #1
avatar+18542 
0

[Hilfe]Vereinfachen Sie folgende beiden Ausdrücke:

 

 

5.1

\(\begin{array}{|rcll|} \hline && \dfrac{1}{1-\frac{1}{p}} - \dfrac{1}{p-1} \\\\ &=& \dfrac{1}{\frac{p}{p}-\frac{1}{p}} - \dfrac{1}{p-1} \\\\ &=& \dfrac{1}{\frac{p-1}{p}} - \dfrac{1}{p-1} \\\\ &=& \dfrac{p}{p-1} - \dfrac{1}{p-1} \\\\ &=& \dfrac{p-1}{p-1} \\\\ &=& 1 \\ \hline \end{array}\)

 

 

5.2

\(\begin{array}{|rcll|} \hline && \dfrac{ \left(-\frac{1}{2}\right)^{-3} \left(\frac{3}{4}\right)^2 x^2 y } { \left(\frac{2}{3}\right)^{-2} \left(-\frac{1}{2}\right) \left(x y\right)^{-2} } \\\\ &=& \dfrac{ \left(\frac{3}{4}\right)^2\left(\frac{2}{3}\right)^{2} x^2 y \left(x y\right)^{2} } { \left(-\frac{1}{2}\right)^{3} \left(-\frac{1}{2}\right) } \\\\ &=& \dfrac{ \left(\frac{3}{4}\right)^2\left(\frac{2}{3}\right)^{2} x^2 y x^2y^2 } { \left(-\frac{1}{2}\right)^{3} \left(-\frac{1}{2}\right)^{1} } \\\\ &=& \dfrac{ \left(\frac{3}{4}\right)^2\left(\frac{2}{3}\right)^{2} x^{2+2} y^{1+2} } { \left(-\frac{1}{2}\right)^{3+1} } \\\\ &=& \dfrac{ \left(\frac{3}{4}\right)^2\left(\frac{2}{3}\right)^{2} x^{4} y^{3} } { \left(-\frac{1}{2}\right)^{4} } \\\\ &=& \dfrac{ \left(\frac{3}{4}\right)^2\left(\frac{2}{3}\right)^{2} x^{4} y^{3} } { \left(-1 \right)^4 \left(\frac{1}{2}\right)^{4} } \\\\ &=& \dfrac{ \left(\frac{3}{4}\right)^2\left(\frac{2}{3}\right)^{2} x^{4} y^{3} } { 1\cdot \left(\frac{1}{2}\right)^{4} } \\\\ &=& \dfrac{ \frac{3^2}{4^2} \cdot \frac{2^2}{3^2} \cdot x^{4} y^{3} } { \left(\frac{1}{2}\right)^{4} } \\\\ &=& \dfrac{ \frac{2^2}{4^2} x^{4} y^{3} } { \left(\frac{1}{2}\right)^{4} } \\\\ &=& \dfrac{ \left(\frac{2}{4}\right)^2 x^{4} y^{3} } { \left(\frac{1}{2}\right)^{4} } \\\\ &=& \dfrac{ \left(\frac{1}{2}\right)^2 x^{4} y^{3} } { \left(\frac{1}{2}\right)^{4} } \\\\ &=& \dfrac{ x^{4} y^{3} } { \left(\frac{1}{2}\right)^{4}\left(\frac{1}{2}\right)^{-2} } \\\\ &=& \dfrac{ x^{4} y^{3} } { \left(\frac{1}{2}\right)^{4-2} } \\\\ &=& \dfrac{ x^{4} y^{3} } { \left(\frac{1}{2}\right)^{2} } \\\\ &=& \dfrac{ x^{4} y^{3} } { \frac{1}{2^2}} \\\\ &=& 2^2x^{4} y^{3} \\\\ &=& 4 x^{4} y^{3} \\ \hline \end{array}\)

 

laugh

heureka 1 hour ago